PENDAMPINGAN MASYARAKAT DI YAYASAN KREASI INSAN NUSANTARA (YAKIN) UNTUK PENJUALAN ONLINE MELALUI MARKETPLACE BUKALAPAK.COM - Rizky Tahara Shita; Wahyu Pramusinto; Lauw Li Hin; Anita Diana; Dwi Achadiani; Fatmasari (Politeknik Negeri Sriwijaya, 2023)
Entrepreneurship is starting to be carried out by the community as well as Small and Medium Enterprises (SMEs) as an alternative to earn income, among others by utilizing information technology and telecommunications. One of the market places, namely Bukalapak, can help small and large entrepreneurs in developing their business to make it more developed. This community service training program aims to make people around the Yayasan Kreasi Insan Nusantara (YaKIN) in East Sudimara Village, Ciledug, Tangerang, able to start an online business with relatively light capital with the Bukalapak market place. Some of the obstacles felt by the surrounding community are the lack of training facilities and teaching staff in the Yayasan Kreasi Insan Nusantara environment, the lack of public interest in online entrepreneurship. Therefore, the use of the internet, technology and telecommunications through Bukalapak online market place sales training, is expected to help the community within the Yayasan Kreasi Insan Nusantara environment to be able to start an online business starting from opening an online store, filling out products and marketing them to earn additional income. In this activity, several stages were carried out to obtain information on initial needs, namely observations, interviews, and literature studies. At the time of the training, using methods, theoretical explanations and practicals directly to participants. The results obtained from this training, the community in the Kreasi Insan Nusantara Foundation environment understands how to manage an online store on Bukalapak.com as a free medium, know and understand Search Engine Optimization techniques in improving online store marketing and its products. Thus, community businesses can increase their sales, and can maximize the marketing of community business products through online marketplaces.